Agama dan Perubahan Sosial - Nesia Mu’asyara; Atik Herawati; Hendika Prayoga; Putri Putri; M. Sopyan; Andini Putri Pangestika; Muldiyansyah Muldiyansyah; Abdul Aziz; Robi Adil (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Religion has a very important role in human life on this earth. Religion functions as a harmonizer of life. In the context of social change, religion directs change for the better. Religious teachings have a great influence in unifying people's perceptions of life. The presence of religion functions as a "social glue", fostering a sense of solidarity, creating peace, social control, bringing society towards safety, changing a person's life into a better life, motivating at work and a set of roles, all of which are in the context of maintaining social stability.